Neotectonic evidence for Late Quaternary reverse faulting in the northern Chile outer forearc (22.5°S-23°S): Implications for seismic hazard. (August 2021) - Cortés-Aranda, J.; González, R.; Fernández, V.; Astudillo, L.; Miller, M.; Molina, D.; Oviedo, A.
Abstract: In the northern Chile outer forearc (19°S to 23°S), extension is the dominant deformation style conducted by crustal faults during the Neogene-Quaternary. Most of this extension has been produced by normal faulting along submeridian branches of the Atacama Fault System (AFS). During the Late Quaternary, several of these faults have built conspicuous metric-scale normal faulting scarps in alluvial deposits; the construction of these scarps has been related, in some cases, to M~7 normal faulting paleoearthquakes. On the contrary, shortening during this time span has only been locally reported. Until now, no metric-scale reverse faulting scarps have been documented along submeridian strands of the AFS. This study presents novel evidence corresponding to reverse fault scarps produced during the Late Quaternary by three NNE and NNW trending faults in the outer forearc between 22.5°S and 23°S: the El Toro (ETF), Caliche (CF), and Sierra Valenzuela (SVF) faults. These scarps, with up to 2.5 m height, developed in basement rocks, pre-Quaternary, and/or Quaternary alluvial deposits. Based on their characteristics and the evidence suggesting that similar fault scarps in the Andean forearc have a seismogenic origin, we interpret that these neotectonic landforms were produced by single reverse faulting paleoearthquakes. Considering the maximum scarp height as a proxy for the coseismic slip and fault length as a proxy for surface rupture length, we have estimated magnitudes between M6.2 and M6.9 for the causative rupture events. To discuss how reverse crustal faulting may be related to the interseismic and/or coseismic stages of the subduction cycle, we perform elastic dislocation models to calculate the horizontal displacement fields (at 0 and 20 km depth) induced by the interplate locking distribution in the area (over a seismic cycle) and three megathrust earthquakes (Antofagasta, 1995, Tocopilla, 2007, and a synthetic rupture). Modeling results suggest that the studied faults may experience reverse slip during both stages of the subduction cycle. We propose that the ETF, CF and SVF are faults capable of producing moderate-to-large earthquakes in the future. Finally, we reinforce the need to address the earthquake potential of the studied faults, and others similar to them, to acquire a complete assessment of the seismic hazard in the northern Chile outer forearc. Highlights: The El Toro, Caliche and Sierra Valenzuela faults are submeridian branches of the Atacama Fault System. These faults have produced metric-scale reverse faulting scarps during the Late Quaternary. Fault scarps are likely due to M6.2 to M6.9 paleoearthquakes. Reverse fault reactivation may occur during the interseismic and/or coseismic stages of the megathrust earthquake cycle.